STUDI PENENTUAN FAKTOR KEAMANAN STABILITAS LERENG MENGGUNAKAN METODE FELLINIUS DAN BISHOP PADA DINDING PENAHAN BATU KALI DI JL. RAYA BEJI PUSKESMAS KOTA BATU - Mau, Jefrianus; Rasidi, Nawir; Hanggara, Ikrar (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Landslides are frequent disasters in the region of Batu, the intensity of heavy rainfall causing unstable slope conditions so that occurrence of landslides in the area of Jl. Raya Beji Puskesmas Kota Batu. The purpose of this study was to determine the safety factor of the smallest on the slope. Slope stability analysis is done using methods Fellinius and Bishop are in the process of the analyst performed using manual calculation table. From the analysis Fellinius methods produce FK = 0.41, FK = 0.30, FK = 0.34 and for the results of the analysis Bishop methods generate FK = 0.34, FK = 0.32, FK = 0.09 show slopes in the location of the landslide-prone state where FK